Notes on Citrogramma Vockeroth and Eosphaerophoria Frey (Diptera: Syrphidae) - Mengual, Ximo (Zootaxa, 2013)
New taxonomic and distributional data on the genera Citrogramma Vockeroth, 1969 and Eosphaerophoria Frey, 1946 are presented, including descriptions of the females of Citrogramma asombrosum Mengual, 2012, Citrogramma pennardsi Mengual, 2012 and Eosphaerophoria dentiscutellata (Keiser, 1958). Modifications to published identification keys to accommodate the new information are provided for both genera.